1990
DOI: 10.1073/pnas.87.16.6161
|View full text |Cite
|
Sign up to set email alerts
|

PC12 cells differentiate into chromaffin cell-like phenotype in coculture with adrenal medullary endothelial cells.

Abstract: Previously we described specific in vitro interactions between PC12 cells, a cloned, catecholaminesecreting pheochromocytoma cell line derived from the rat adrenal medulla, and bovine adrenal medullary endothelial cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…PC12 cells are derived from a rat pheochromocytoma tumor able to differentiate into mature chromaffinic cells or into sympathetic neuronlike cells, depending on the external stimuli [Greene and Tischler, 1982;Guroff, 19851. Besides this property, this cell line is rich in bioactive peptides such as opioid peptides, neurotensin, and dynorphin, whose level are modulated during differentiation to one or another phenotype Byrd et al, 1987;Mizrachi et al, 1990;Margioris et al, 19921. We hypothesized that if EOPA acts as a bioactive peptide metabolizing enzyme: (1) we would be able to detect its presence in PC12 cells; (2) since the level of bioactive peptides changes according to PC12 differentiation, we inferred that EOPA activity would also be modulated during differentiation to one or another pathway.…”
Section: Nh2) Is Cleaved Generating [Met51-enkephalinmentioning
confidence: 98%
“…PC12 cells are derived from a rat pheochromocytoma tumor able to differentiate into mature chromaffinic cells or into sympathetic neuronlike cells, depending on the external stimuli [Greene and Tischler, 1982;Guroff, 19851. Besides this property, this cell line is rich in bioactive peptides such as opioid peptides, neurotensin, and dynorphin, whose level are modulated during differentiation to one or another phenotype Byrd et al, 1987;Mizrachi et al, 1990;Margioris et al, 19921. We hypothesized that if EOPA acts as a bioactive peptide metabolizing enzyme: (1) we would be able to detect its presence in PC12 cells; (2) since the level of bioactive peptides changes according to PC12 differentiation, we inferred that EOPA activity would also be modulated during differentiation to one or another pathway.…”
Section: Nh2) Is Cleaved Generating [Met51-enkephalinmentioning
confidence: 98%
“…Indeed, cancer cell/stromal cell interaction plays a crucial role in tumor growth and evolution, affecting gene transcription, differentiating and apoptotic pathways (Mauro et al 1994;Inouc et al 2001;Dong-Le Bourhis et al 1997;Lin et al 1998), though little is known about the mechanism through which host cells interfere with cancer growth; cell-to-cell communication-mediated tumor growth inhibition appears to be very tissue-specific, and it should also be borne in mind that host-tumor interaction is not a one-way process (Krutovskikh 2002). Normal cells located in the wrong tissue degenerate into cancer cells (Biskind and Biskind 1944), whereas neoplastic cells introduced into a blastocyst (Brinster 1974;Mintz and Illmensee 1975;Hochedlinger et al 2004), co-cultured with normal cells (Mizrachi et al 1990), implanted into a normal microenvironment (Mc Cullogh et al 1997) or subjected to differentiating (Missale et al 1998;Bizzarri et al 2003;Sell and Pierce 1994;Wang et al 2002) and embryonic signals (Lee and Herlyn 2006;Lee et al 2005;Cucina et al 2006), either undergo apoptosis or become normal, thereafter contributing to the development of organised ''normal'' bodily structure. Moreover, some preliminary data have shown that differentiating-based treatment responds significantly both in vivo (Yu and Tsai 2001) and in clinical trials (Livraghi et al 2005;Sell 2004).…”
Section: Reversibility Of Cancer Transformationmentioning
confidence: 95%
“…PC 12 cells were cultured in DMEM (4.5 g/1 glucose) supplemented with 7.5% FCS and 7.5% horse serum, 2.5 mM Lglutamine, and antibiotics, as previously described (12,13).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Bovine adrenal medullary microvascular endothelial cells (BAME) were grown in Earl's modified Eagle's medium (EMEM, 1 g/1 glucose), supplemented with 10% FCS, 2.5 mM L-glutamine, 30 gg/ml ECGS, 2 Iag/ml heparin, and the antibiotics cocktail described above (12,13).…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation